STUDENTS’ WRITING SKILLS OF THE ENGLISH DEPARTMENT AT MUHAMMADIYAH SIDRAP UNIVERSITY - Sakkir, Geminastiti (Uniqbu Journal of Social Sciences, 2023)
This study aims to determine students' writing skills by using a test instrument, a descriptive text writing test on students' writing skills. This study uses quantitative research with a descriptive quantitative design. The target population in this study was the English Department of Muhammadiyah Sidrap University. The researchers used cluster sampling to select a representative sample and represent the population. Thus, the researchers took one class as a sample to analyze. The sample was the third semester, which consisted of 35 students. In the writing test, the researchers found that out of 35 students in the third semester of the English Department of Sidrap Muhammadiyah University, no student was categorized as good, twenty-nine students were classified as fair, and six were classified as poor.